Preliminary Study on Heavy Metals in Coconut and Coconut Products - Warsakoon, W.M.M.P.D.K. (International Coconut Community Journal, 2010)
Coconut is one of the major plantation crops which plays a pivotal role in the economy of Sri Lanka. The objective of this study is to investigate the presence of heavy metals in fresh coconut kernel and in some coconut products in Sri Lanka. Levels of lead (Pb), Chromium (Cr), Aluminum (Al), Ferrous (Fe), Copper (Cu), Manganese (Mn), Cadmium (Cd), Zinc (Zn), and Arsenic (As) were determined in samples of fresh coconut kernel, coconut milk, coconut milk powder, and coconut cream using the Atomic Absorption Spectrometer (AAS) method. Fresh coconut kernel and coconut products were found to contain Fe, Zn, Cu and Mn. Fresh coconut kernels showed the highest content of these metals. Coconut cream and coconut milk samples demonstrated the lowest levels of these metals. Potentially toxic heavy metals such as Pb, Cd, As, and Al were not detected in the tested samples. The occurrence of the heavy metals in all the coconut products tested was below the permissible levels suggested by the USDA, World Health Organization, and the Quality Standards of CODEX Vol. 1 Section 6, 1991.